Viskositas, Keasaman, Warna, dan Sifat Organoleptik Yogurt Susu Kambing yang Diperkaya dengan Ekstrak Beras Hitam - Fani Dwi Evadewi; Citopartusi Margaluna Purnama Tjahjani (Universitas Batanghari Jambi, 2021)
Goat milk yogurt with the addition of black rice extract can increase the functionality of goat milk yogurt and is a functional food as a source of antioxidants. As is well known that black rice has a deep black color, due to the presence of anthocyanins. The benefits possessed by black rice is to prevent the onset of degenerative diseases. The purpose of this study was to evaluate the enrichment of goat's milk yogurt with the addition of black rice extract in terms of physical characteristics including viscosity, storage, color and organoleptic. This study is an experimental study with 5 treatments and 5 replications, so that 25 experimental trials were obtained, 5 treatments were administered with black rice extract with control, 5%, 10%, 15%, 20%. The results showed that the addition of up to 20% black rice extract to goat's milk yogurt goat's milk yogurt with pH characteristics resulted in pH values ranging from 3.7 to 4.1; the more addition of black rice extract can reduce the viscosity value of yogurt and the highest brightness (L*) is found in (P0) without the addition of black rice extract, which is 75.76, the red color (a*) of milk yogurt is highest in (P4) with the addition of 20% black rice extract was 13.20 and the yellow color (b*) of goat's milk yogurt with the highest addition of black rice extract was at P0 (without the addition of black rice extract) of 4.94. The organoleptic properties of goat's milk yogurt with the addition of black rice extract are favored by consumers because of the potential health benefits and high nutritional value.